Major elements distribution in the soil profile of petroleum contaminated soils - Sattar, Shehla; Siddiqui, Samina; Jan, Irfan U. (Journal of Himalayan Earth Sciences, 2018)
Information about the effect of petroleum waste contamination on soil physicochemical characteristics and major elements concentration in soil is in scarcity. The objective of this study was to understand that petroleum waste contamination can improve the major elements concentrations in soils. This can be evaluated with the changes in the pH, EC and organic carbon content in the soils. For that purpose, soil samples (n=57) were collected at three depths within a soil profile of all sites of the study areas. Physicochemical parameters studied in all soils were pH, EC, OC, and major elements (Ca, Mg, Al, K, Na and P). Petroleum waste contamination had no effect on soil physicochemical characteristics except for soil organic carbon content. Soil organic carbon content increases with petroleum waste contamination. There was no correlation between the soil organic carbon and major elements content in any of the soil of both the study areas. It was noted in this study that all soils of Kohat Plateau were sufficient in calcium and sodium, whereas phosphorus and potassium were found to be deficient in such soils. Aluminum was found to be marginal in all soils. Petroleum waste contamination poses no effect on the lateral and horizontal distribution of all major elements in any of the soil profile of both the study areas. However, calcium was found to be decreases with increase in depth in a soil profile and distance from the contamination source. This suggests that petroleum waste may increase the concentration of Ca in the soil. It was observed that pH showed a positive correlation with calcium and potassium, this suggests that calcium and potassium is pH dependent in all soils. Petroleum waste contamination poses no effect on major elements concentrations in all soils. Organic carbon content increases with the petroleum contamination except for a few exceptions.